2022
DOI: 10.1186/s41205-022-00147-7
|View full text |Cite
|
Sign up to set email alerts
|

From the ground up: understanding the developing infrastructure and resources of 3D printing facilities in hospital-based settings

Abstract: Background 3D printing is a popular technology in many industries secondary to its ability to rapidly produce inexpensive, high fidelity models/products, mainly through layer-by-layer fusion of various substrate materials. In healthcare, 3D printing has garnered interest for its applications in surgery, simulation, education, and medical device development, and 3D printing facilities are now being integrated into hospital-based settings. Yet, little is known regarding the leadership, resources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Advances in accessible 3D printing technology, in parallel to data handling and integrated storage systems, known in healthcare settings as 'picture archiving and communication systems' (PACS), are enabling hospitals and healthcare facilities to now rapidly translate imaging data out of the digital domain and into the physical domain (Fig. 1) [5]. To produce a 3D printed model from patient scan data, one must first obtain the scan data in a compatible format, such as a DICOM file, generated as the output viewing format from a variety of medical imaging techniques, such as computed tomography (CT) or magnetic resonance imaging (MRI) (Fig.…”
Section: Background To 3d Printing Anatomical Modelsmentioning
confidence: 99%
“…Advances in accessible 3D printing technology, in parallel to data handling and integrated storage systems, known in healthcare settings as 'picture archiving and communication systems' (PACS), are enabling hospitals and healthcare facilities to now rapidly translate imaging data out of the digital domain and into the physical domain (Fig. 1) [5]. To produce a 3D printed model from patient scan data, one must first obtain the scan data in a compatible format, such as a DICOM file, generated as the output viewing format from a variety of medical imaging techniques, such as computed tomography (CT) or magnetic resonance imaging (MRI) (Fig.…”
Section: Background To 3d Printing Anatomical Modelsmentioning
confidence: 99%
“…A recent survey study of hospital 3D printing sites—primarily represented by large, North American, university-affiliated institutions—found that just over half of respondents reported having a single print lab site versus multiple locations, and, of those with a primary administrative department, 67% identified Radiology as the managing group. 3 In our institution, for example, we have adopted a centralized 3D printing lab which is managed by BME. This was chosen due to technical resources within the BME group and strong existing clinical relationships between BME and Radiology, Radiation Oncology, Surgery, and other key users of 3DP technology.…”
Section: Centralized 3d Printingmentioning
confidence: 99%
“… 1 Although relatively sparse, there is some literature discussing various aspects of regulatory requirements, organizational structure, and considerations for hospital practice surrounding 3D printing. 2 4 It can be difficult when planning implementation of a 3D printing operation to consolidate the relevant information and considerations. There is a need for introductory overviews intended not just for advanced medical/technical specialists, but also for others in a hospital organization including administrators, leaders, healthcare providers, and others who may not be as familiar with the details required to adopt this technology.…”
Section: Introductionmentioning
confidence: 99%
“…One such evolving area is 3D printing, which has recently been gaining significant traction in its clinical applications. Within just the last decade, an increasing number of 3D printing labs have been established, typically within large, university-affiliated teaching hospitals [ 5 ]. Clinical applications for 3D printing are broad and range from perioperative planning via procedural stimulation to medical student anatomy education, and the use of 3D printing has led to improvements in quality of trainee comprehension and patient outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%